Composite conductive powder material and preparation method and application thereof

By using composite conductive powder materials and coating the metal powder core with anti-permeability materials, the problem of cell efficiency degradation caused by diffusion between metal electrodes and perovskite layers in perovskite solar cells is solved, and low-cost electrodes are provided materials, achieving improved battery efficiency and reduced production costs.

CN119339986APending Publication Date: 2025-01-21AUNER OPTOELECTRONIC TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310861122.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In perovskite solar cells, the diffusion of metal and halide ions between the metal electrode and the perovskite layer leads to degradation of battery efficiency, and traditional silver powder or silver-clad copper powder electrode materials are costly and difficult to produce on a large scale.

Method used

A composite conductive powder material is used, which is composed of a powder core formed of metal materials and a coating layer formed of anti-penetration materials. The coating layer blocks the diffusion of metal and external materials, ensuring conductivity and reducing the escape of metal ions.

Benefits of technology

It effectively avoids or alleviates the battery efficiency degradation problem caused by the use of metal electrode materials in perovskite or perovskite stacked cells, while reducing production costs and providing a low-cost electrode material solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119339986A_ABST
    Figure CN119339986A_ABST
Patent Text Reader

Abstract

The invention discloses a composite conductive powder material and a preparation method and application thereof, and relates to the technical field of solar cells. The composite conductive powder material provided by the invention comprises a powder core formed by a metal material; the coating layer is formed by an anti-permeation material, the coating layer at least partially coats the powder core, and the anti-permeation material is used for preventing metal of the powder core from diffusing to the outside of the coating layer and preventing other materials located outside the coating layer from diffusing to the powder core. The powder material can be used as a raw material for low-cost electrode preparation methods such as screen printing, laser transfer printing, printing or coating, and can solve the problem of cell efficiency degradation caused by chemical reaction between metal of a metal electrode and a material of a photoelectric conversion layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a composite conductive powder material and a preparation method and application thereof. Background Art

[0002] Organic-inorganic hybrid perovskites have excellent properties such as large absorption coefficient, small exciton binding energy, long carrier diffusion length, and high carrier mobility. As an ideal photovoltaic absorption material, they have attracted widespread attention. Since the first report of perovskite solar cells in 2009, the power conversion efficiency of perovskite solar cells has rapidly increased from the initial 3.8% to 25.7%, which is comparable to commercial single-crystal silicon solar cells. At present, the conversion efficiency of perovskite / crystalline silicon solar cells has increased to 33.7%.

[0003] Solar cells generally use high-conductivity metal electrodes, but for perovskite solar cells (or stacked cells containing perovskite subcells), the mutual diffusion of metal and halogen ions between the metal electrode and the perovskite layer will induce cell efficiency degradation. Specifically, the halogens in the perovskite light-absorbing layer may diffuse to the metal electrode, and the metal electrode will be oxidized by the halogen, resulting in an increase in the contact resistance of the electrode; at the same time, the metal elements of the metal electrode migrate to the perovskite light-absorbing layer, which will also affect the light absorption efficiency and stability of the perovskite light-absorbing layer, ultimately leading to cell efficiency degradation.

[0004] In addition to efficiency and stability, cost is also one of the important factors for the success of large-scale production of solar cells. In terms of electrodes and electrode leads, screen printing technology is currently a low-cost and feasible electrode preparation method. The metal paste currently used in this technology is mainly made of silver powder or silver-coated copper powder. If used in perovskite cells or perovskite-related stacked cells, there is the above-mentioned problem of cell efficiency degradation induced by the mutual diffusion of metal in the metal electrode and halide ions in the perovskite layer.

[0005] Therefore, there is an urgent need for a low-cost electrode material that can avoid or at least partially solve the problem of cell efficiency degradation induced by the use of metal electrode materials in perovskite or perovskite tandem cells.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a composite conductive powder material and a preparation method and application thereof, aiming to avoid or alleviate to a certain extent the problem of battery efficiency degradation induced by the use of metal electrode materials in perovskite and perovskite stacked cells.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a composite conductive powder material, comprising:

[0010] A powder core formed of a metallic material; and,

[0011] The coating layer is formed by the anti-penetration material, and the coating layer at least partially covers the powder core. The coating layer is used to prevent the metal in the powder core from diffusing to the outside of the coating layer and other materials outside the coating layer from diffusing to the powder core.

[0012] In an optional embodiment, the composite conductive powder material has a core-shell structure, and the coating layer completely covers the powder core.

[0013] In an optional embodiment, the anti-permeability material is at least one of a conductive ceramic material and graphene, and may be any one or more of the above.

[0014] In an optional embodiment, the conductive ceramic material includes at least one of TiN, TiC, TiCN, TiSiN, AlTiN, ZrN, TaN and HfN, and the conductive ceramic material may be any one or more of the above.

[0015] For example, the coating layer may be a laminated structure composed of a plurality of conductive ceramic materials, or may be formed by mixing a plurality of conductive ceramic materials.

[0016] In an optional embodiment, the composite conductive powder material further includes an adhesion layer, which is located between the powder core and the coating layer, and the adhesion layer is used to increase the adhesion between the coating layer and the powder core. Optionally, the thickness of the adhesion layer is 5nm to 30nm, such as 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc.

[0017] In an optional embodiment, when the coating layer is a conductive ceramic material, the adhesion layer includes at least one of a titanium metal layer, a chromium metal layer and a titanium-chromium composite layer.

[0018] In an optional embodiment, the powder core includes at least one of metal single substance particles and alloy particles, and may be metal single substance particles, may be alloy particles, or may be a mixture of the two.

[0019] Optionally, the powder core includes at least one of silver particles, copper particles and silver-coated copper particles, that is, it can be any one or more of the above.

[0020] In an optional embodiment, the particle size or equivalent particle size of the composite conductive powder material is less than 35 μm, such as 34 μm, 30 μm, 25 μm, 20 μm, 15 μm, 10 μm, 5 μm, 3 μm, 2 μm, 1 μm, 0.5 μm, etc. Optionally, the particle size or equivalent particle size of the composite conductive powder material is 1 μm-3 μm.

[0021] Further optionally, the composite conductive powder material satisfies: D50 is 1 to 3 μm and D90 is 8 to 10 μm.

[0022] In an optional embodiment, the coating layer has a thickness of 5 nm to 1 μm, and optionally, the coating layer has a thickness of 50 nm to 0.3 μm. Specifically, the coating layer may have a thickness of 5 nm, 10 nm, 50 nm, 100 nm, 300 nm, 500 nm, 800 nm, 1000 nm (i.e., 1 μm), etc.

[0023] In a second aspect, the present invention provides a method for preparing a composite conductive powder material according to any one of the aforementioned embodiments, comprising:

[0024] Provide metal material as the core of the powder;

[0025] A coating layer made of an anti-permeation material is formed on the powder core, so that the coating layer at least partially covers the powder core.

[0026] In an optional embodiment, a coating layer can be formed on the powder core using a powder coating device, but is not limited to the above method. Optionally, the powder coating device includes at least one of a powder magnetron sputtering coating device, a powder cathode arc coating device, an atomic layer deposition device, and a chemical vapor deposition device, and can be any one or more of the above.

[0027] In an optional embodiment, the process of forming a coating layer on the powder core using a powder coating device includes: using a magnetron sputtering method to first form a 10nm to 20nm adhesion layer on the powder core; and then forming a coating layer on the adhesion layer using a magnetron sputtering method.

[0028] The composite conductive powder material according to any one of the above items is used as a raw material for preparing electrodes or electrode leads of solar cells.

[0029] In a third aspect, use of any one of the composite conductive powder materials in the above embodiments in preparing a conductive structure;

[0030] Optionally, the conductive structure includes a solar cell electrode, an electrode lead or a grid line.

[0031] In a fourth aspect, the present invention provides a conductive material for a solar cell, comprising a composite conductive powder material according to any one of the aforementioned embodiments or a composite conductive powder material prepared by any one of the preparation methods according to the aforementioned embodiments; the conductive material comprises a conductive paste and a conductive ink.

[0032] In an optional embodiment, when the conductive material is a conductive paste, the conductive paste further comprises: an organic polymer binder phase, an organic solvent and an additive;

[0033] Optionally, the organic polymer bonding phase includes a resin and a curing agent that matches the resin, and the resin includes at least one of epoxy resin, acrylic resin, polyurethane, cellulose, silicone resin and rosin; that is, the organic polymer bonding phase includes one or more of epoxy resin, acrylic resin, polyurethane, cellulose, silicone resin and rosin, and the organic polymer bonding phase also includes a curing agent that matches the epoxy resin, acrylic resin, polyurethane and silicone resin;

[0034] Optionally, the organic solvent includes at least one of esters, ethers, ketones and hydrocarbons;

[0035] Optionally, the auxiliary agent includes at least one of a coupling agent, a plasticizer, a defoaming agent, a thixotropic agent and a wetting agent.

[0036] It should be noted that the specific amounts of the organic polymer binder phase, organic solvent and additives are not limited and can be adjusted according to demand.

[0037] In an optional embodiment, in the conductive paste, the composite conductive powder material includes a main powder and a doped powder with different particle sizes, the average particle size of the main powder is 2μm to 3μm (such as 2.0μm, 2.5μm, 3.0μm, etc.), and the average particle size of the doped powder is smaller than the average particle size of the main powder, that is, a method of doping small particles of doped powder in a main powder with a large particle size can be adopted. Optionally, the average particle size of the doped powder is 10nm to 100nm (such as 10nm, 30nm, 50nm, 80nm, 100nm, etc.). Optionally, the mass proportion of the main powder in the composite conductive powder material is greater than or equal to 70%.

[0038] In a fifth aspect, the present invention provides a solar cell, wherein the electrode is made of the composite conductive powder material of any one of the aforementioned embodiments or the conductive material for a solar cell of any one of the aforementioned embodiments.

[0039] In an optional embodiment, the solar cell includes a perovskite cell, an all-perovskite tandem cell, or a perovskite crystalline silicon tandem cell.

[0040] The present application provides a composite conductive powder material and a preparation method and application thereof, wherein an anti-permeation material is coated with a metal material that is chemically active, easy to diffuse but has high electrical conductivity. This structure can not only ensure the overall electrical conductivity of the material, but also reduce the escape of metal ions in the material. It can be used as a raw material for low-cost large-scale electrode preparation methods (such as screen printing, laser transfer, or printing technology, or electrostatic spraying and other film-forming methods), and can avoid or to a certain extent alleviate the cell efficiency degradation induced by the use of metal electrodes in impurity-sensitive solar cells (such as perovskite and perovskite stacked cells, copper indium gallium selenide cells).

[0041] Specifically, when the composite conductive powder material is used to prepare electrodes or other conductive layers of solar cells, the powder core formed by the metal material can ensure the conductivity of the material; the anti-permeation material is coated with the metal material that is easy to diffuse and chemically active. Even if the material of the photoelectric conversion layer or other layers (such as the halogen element or ion of the perovskite light absorption layer) migrates to the electrode or conductive layer made of the composite conductive powder material, due to the blocking effect of the anti-permeation material, the metal core of the composite conductive powder material there will not react with it, thereby reducing the impact on the conductivity of the electrode (or conductive layer); at the same time, the coating layer of the anti-permeation material can also block the metal of the metal core from diffusing outward, thereby preventing the metal from entering the photoelectric conversion layer (such as the perovskite light absorption layer, or the copper indium gallium selenide light absorption layer) and affecting its stability.

[0042] The composite conductive powder material of the present application is low in price and has good oxidation resistance. It can be used as a raw material for screen printing, laser transfer, printing or other coating film forming methods. For example, it can replace silver powder or silver-coated copper powder to prepare low-temperature conductive slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 A schematic structural diagram of a composite conductive powder material provided in Example 1 of the present application;

[0045] Figure 2 A schematic structural diagram of another composite conductive powder material provided in Example 1 of the present application;

[0046] Figure 3 A schematic structural diagram of another composite conductive powder material containing an adhesion layer provided in Example 1 of the present application;

[0047] Figure 4 A schematic diagram of the preparation process of the composite conductive powder material provided in Example 2 of the present application;

[0048] Figure 5 Contact resistance test diagram of copper wire with titanium nitride coating provided for the simulation experiment of this application.

[0049] Icon: 21-powder core; 22-coating layer; 23-adhesion layer. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Perovskite

[0052] The term "perovskite" refers to a material with a structure similar to CaTiO3. The structure of CaTiO3 can be represented by the molecular formula ABX3, where A and B represent cations of different sizes, and X is an anion. In the unit cell, the A cation is located at (0, 0, 0), the B cation is located at (1 / 2, 1 / 2, 1 / 2), and the X anion is located at (1 / 2, 1 / 2, 0). The A cation is usually larger than the B cation.

[0053] The skilled person will appreciate that A, B and X can be varied to distort the structure of the perovskite material from that adopted by CaTiO3 to a less symmetrical distorted structure. If the material includes layers having a structure similar to that of CaTiO3, the symmetry will also be reduced.

[0054] The skilled person will appreciate that the perovskite material can be represented by the formula [A][B][X]3, wherein [A] is at least one cation, [B] is at least one cation, and [X] is at least one anion. When the perovskite includes more than one A cation, different A cations can be distributed on the A sites in an ordered or disordered manner. When the perovskite includes more than one B cation, different B cations can be distributed on the B sites in an ordered or disordered manner. When the perovskite includes more than one X anion, different X ions can be distributed on the X sites in an ordered or disordered manner. The symmetry of a perovskite including more than one A cation, more than one B cation, or more than one X cation will generally be lower than the symmetry of CaTiO3.

[0055] In general, as used herein, the term "perovskite" refers to (a) a material having a three-dimensional crystal structure similar to that of CaTiO3; or, (b) a material comprising a material layer, wherein the material layer has a structure similar to that of CaTiO3. Although both types of perovskites can be used in devices according to the present application, the first type of perovskite (a), i.e., a perovskite having a three-dimensional (3D) crystal structure, can be preferably used. Such perovskites generally include a 3D network of perovskite unit cells without any separation between layers. On the other hand, the second type of perovskite (b) includes perovskites having a two-dimensional (2D) layered structure. Perovskites having a 2D layered structure may include layers of perovskite unit cells separated by (intercalated) molecules; an example of such a 2D layered perovskite is [2-(1-cyclohexenyl)ethylammonium]2PbBr4. 2D layered perovskites tend to have higher exciton binding energies, which is conducive to the generation of bound electron-hole pairs (excitons) rather than free charge carriers under photoexcitation. The bound electron / hole pairs may not be sufficient to move to the p-type or n-type contacts, where they can transfer (ionize) and generate free charges. Therefore, in order to generate free charges, the exciton binding energy must be overcome, which represents the energy cost of the charge generation process and leads to lower voltage and lower efficiency in photovoltaic cells. In contrast, perovskites with 3D crystal structures tend to have much lower exciton binding energies (on the scale of thermal energy) and can therefore generate free carriers directly after photoexcitation. Therefore, the perovskite semiconductors used in the devices and methods of the present invention are preferably perovskites with three-dimensional crystal structures.

[0056] In a preferred embodiment, the perovskite material has the general formula [A][B][X]3, wherein [A] is one or more monovalent cations, [B] is one or more divalent inorganic cations, and [X] is one or more halide anions, preferably selected from fluoride, chloride, bromide and iodide, and further preferably selected from chloride, bromide and iodide. More preferably, [X] comprises one or more halide anions selected from bromide and iodide. [A] preferably comprises one or more halide anions selected from methylammonium (CH3NH3 + ), formamidine (HC(NH)2)2 + ) and ethylammonium (CH3CH2NH3 + ) and preferably comprises an organic cation selected from methylammonium (CH3NH3 + ) and formamidine (HC(NH)2)2 + ) organic cation. [A] may include one or more selected from Cs + , Rb + , Cu + , Pd + , Pt + 、Ag+ 、Au + , Rh + And Ru + [B] preferably comprises at least one selected from Pb 2+ and Sn 2+ divalent inorganic cations, and preferably include Pb 2 +. For example, Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 includes two A-site ions and two X-site ions.

[0057] As used herein, the term "perovskite light absorbing layer" refers to a functional film layer made of a perovskite material that can absorb light and thereby generate free charge carriers. However, the perovskite material can be a perovskite material that can emit light by accepting charges (electrons and holes), which are then recombined and emit light.

[0058] The technician will understand that the perovskite material used in the present invention can be a perovskite that acts as an n-type electron transport semiconductor when light doped. Alternatively, it can be a perovskite that acts as a p-type hole transport semiconductor when light doped. Therefore, the perovskite can be n-type or p-type, or it can be an intrinsic semiconductor. In a preferred embodiment, the perovskite used is a perovskite that acts as an n-type electron transport semiconductor when light doped. The perovskite material can exhibit bipolar charge transport and therefore act as an n-type semiconductor and a p-type semiconductor. Specifically, the perovskite can act as an n-type semiconductor and a p-type semiconductor depending on the type of junction formed between the perovskite and the adjacent material. Typically, the perovskite semiconductor used in the present invention is a photosensitive material, i.e., a material capable of photogenerated and charge transport.

[0059] Perovskite solar cells

[0060] At present, perovskite solar cells mainly include single-junction perovskite cells and tandem perovskite cells. Among them, single-junction perovskite cells are multi-layer structures that only include one perovskite film layer as a photoelectric conversion layer (generally including an electron transport layer, a perovskite light absorption layer, a hole transport layer, and an electrode layer, etc.), while tandem perovskite cells include crystalline silicon / perovskite tandem cells, all-perovskite tandem cells, thin-film cells (such as copper indium gallium selenide) / perovskite tandem cells, etc.

[0061] Exemplarily, the perovskite light absorbing layer in the perovskite solar cell may include any one of the following: FACsPbIBrCl, FAMACsPbIBrCl, FACsDMAPbIBrCl, CsDMAPbIBrCl, FACsPbIBr, FAMACsPbIBr, FACsDMAPbIBr, CsDMAPbIBr, FACsPbI, FAMACsPbI, FACsDMAPbI, CsDMAPbI, FACsPbSnI, FAMACsPbSnI, FACsDMAPbSnI and CsDMAPbSnI. If more than two A-site ions (or B-site ions, or X-site ions) are included, the ratio of the two or more A-site ions can also be changed as needed.

[0062] For example, the perovskite light absorbing layer can be methylammonium lead trihalide CH3NH3PbX3, where X is a halogen ion, such as iodide, bromide or chloride. The optical band gap of the perovskite is between about between (depending on the halide content).

[0063] Halide perovskite materials are highly corrosive to almost all metals. Electrode materials such as gold, silver, copper, aluminum and chromium commonly seen in the literature will undergo irreversible chemical reactions with halide perovskites under certain conditions (light, heat, bias, atmosphere). As the battery device ages, the corroded metal electrode will pass through the interface layer and slowly penetrate into the perovskite light-absorbing layer, doping the perovskite film and causing deep energy level defects, leading to irreversible deterioration of device performance. In addition, the halogen in the perovskite light-absorbing layer will diffuse to the metal electrode, which will be oxidized by the halogen, resulting in an increase in the contact resistance of the electrode.

[0064] Based on the above technical problems, this application provides the following technical solutions.

[0065] Embodiment 1

[0066] like Figure 1 As shown, an embodiment of the present application provides a composite conductive powder material, comprising: a powder core 21 formed of a metal material; and a coating layer 22 formed of an anti-permeation material. The coating layer 22 at least partially coats the powder core 21. The coating layer 22 is used to prevent the metal of the powder core 21 from diffusing to the outside of the coating layer 22 and other materials outside the coating layer 22 from diffusing to the powder core 21.

[0067] The shape of the composite conductive powder material is preferably spherical or nearly spherical, but is not limited thereto. For example, the composite conductive powder material can also be in the form of flakes or dendrites. Alternatively, the spherical or nearly spherical shapes account for the majority (for example, more than 60%) of the composite conductive powder, and flake or dendrite powders are mixed in. Figure 2 As shown, a sheet-like composite conductive powder material is shown.

[0068] The material and thickness of the coating layer 22 are not specifically limited herein, as long as a dense film layer sufficient to prevent the diffusion of the material can be formed. Therefore, the anti-permeability material herein refers to a material that can form a dense film layer, and the density of the film layer is based on the ability to prevent or to some extent hinder the mutual diffusion between the metal material of the powder core 21 and other materials outside the coating layer 22.

[0069] Those skilled in the art should understand that, although there is a coating layer 22, the existence of the coating layer 22 does not change the conductivity of the material itself, and the conductive material such as conductive paste or conductive ink made of the powder material containing the coating layer 22 of the present application still meets the conductivity requirements. The anti-penetration material used in the coating layer 22 is preferably a conductive material.

[0070] Preferably, the anti-permeability material is a conductive ceramic material or graphene. After the conductive ceramic material and graphene are made into a coating layer, they both have excellent anti-permeability and can prevent metal materials and other materials outside the coating layer 22 from passing through the coating layer. Exemplarily, the conductive ceramic material can be one of the following, or a mixture of multiple thereof, or a laminated structure formed by multiple conductive ceramic materials: TiN, TiC, TiCN, TiSiN, AlTiN, ZrN, TaN and HfN.

[0071] In the composite conductive powder material of the present application, the core of the powder material is formed by a metal material, and the coating layer formed by an anti-penetration material at least partially covers the metal core. The metal accounts for a relatively large proportion in the entire material, which can ensure that the overall conductivity of the electrode layer or the conductive layer made of the composite conductive powder material meets the design requirements. Moreover, since it does not contain precious metals, is low in price, and has good oxidation resistance, it can replace silver powder or silver-coated copper powder for low-temperature slurry.

[0072] When the composite conductive powder material of the present application can be used in the electrode layer (or conductive layer) of a solar cell or other device, it can reduce the impact of the escape of metal ions in the electrode layer (or conductive layer) on the device performance, and can also reduce the impact of the outward diffusion of the solar cell light-absorbing layer material on the conductive performance of the electrode layer (or conductive layer), thereby improving the stability of the solar cell or other device.

[0073] The composite conductive powder material of the present application can be used to prepare photovoltaic conductive slurries and conductive structures such as electrodes, electrode leads, grid lines, bus bars and interconnection bars, but is not limited to this. It can also be applied to shielding materials or coatings, as well as hard coating materials with conductive requirements.

[0074] Among them, preferably, Figure 1 As shown, the composite conductive powder material has a core-shell structure, and the coating layer 22 formed by the anti-permeation material completely covers the powder core 21, at which time the anti-permeation effect is optimal.

[0075] Furthermore, if Figure 3 As shown, in other embodiments, the composite conductive powder material may further include an adhesion layer 23, and the adhesion layer 23 is located between the powder core 21 and the coating layer 22. The adhesion layer 23 serves as a transition layer between the metal and the conductive ceramic, and can enhance the adhesion between the powder core 21 and the coating layer 22. Exemplarily, the coating layer 22 may be a conductive ceramic material, and the adhesion layer 23 may be a titanium metal layer, or a chromium metal layer, or a titanium-chromium composite layer. Among them, the powder core 21 may be a metal single substance particle or an alloy particle, such as a silver particle, a copper particle, or a silver-coated copper particle. Of course, the powder core 21 may also be other metal particles such as nickel, copper, etc.

[0076] Exemplarily, a composite conductive powder material is provided, wherein copper metal particles serve as the powder core 21, the periphery of the copper metal particles is covered with a titanium adhesion layer, and the periphery of the titanium adhesion layer is covered with a titanium nitride coating layer.

[0077] In some embodiments, the particle size or equivalent particle size of the composite conductive powder material is less than 35 μm. Preferably, the particle size or equivalent particle size of the composite conductive powder material is less than 3 μm, such as 1 to 3 μm.

[0078] In some embodiments, the maximum particle size of the composite conductive powder material does not exceed 20 microns, preferably 10 microns. In different fields and different usage scenarios and film forming methods, the particle size requirements of the composite conductive powder material are different. The composite conductive powder material used in the spraying process is generally larger, and the maximum particle size is generally less than 35μm. For example, the antistatic film used for electrostatic shielding, the particle size of the powder material required when plasma spraying is generally 20-35μm.

[0079] For example, in the field of microelectronics, the maximum particle size of composite conductive powder materials used for screen printing is generally less than 20 microns, preferably less than 10 microns. Generally, the powder is mainly 0.5 to 3 microns, and a small amount of 20 to 200 nm nano-particles are doped.

[0080] Conductive pastes used in film formation such as screen printing, laser transfer, and printing are generally a mixture of powders with a particle size of 2 to 3 μm. Common conductive paste particle sizes include one D50, 7 to 15 microns; one D50, 1 to 5 microns; and another D50, 10 to 200 nanometers.

[0081] In some embodiments, the composite conductive powder material is formed by mixing powder materials of two or more particle sizes. The powder material with a smaller particle size has good film adhesion, and the powder material with a larger particle size has high film conductivity. When two or more powder materials with different particle sizes are mixed, the particles with a smaller particle size fill the gaps between the particles with a larger particle size, resulting in high conductivity and good film quality. An exemplary composite conductive powder material satisfies: D50 is 1 to 3 μm and D90 is 8 to 10 μm.

[0082] In some embodiments, the coating layer has a thickness of 5 nm to 1 μm, preferably 50 nm to 0.3 μm.

[0083] The present application also provides the use of any of the composite conductive powder materials in the aforementioned embodiments in the preparation of a conductive structure; in particular, in the conductive structure of a solar cell. The conductive structure may include a solar cell electrode, an electrode lead or a grid line. This powder material can be used as a raw material for low-cost electrode preparation methods such as screen printing, laser transfer, printing or coating, and can solve the problem of cell efficiency degradation caused by chemical reactions between the metal of the metal electrode and the material of the photoelectric conversion layer.

[0084] Illustratively, the composite conductive powder material according to any of the above items can be made into conductive paste or conductive ink, used for preparing electrodes or electrode leads of solar cells, or forming solder strips and solders for connecting the conductive structures of solar cells.

[0085] This embodiment also provides an electrode material for a solar cell, comprising any of the above composite conductive powder materials.

[0086] Any of the above composite conductive powder materials can be made into conductive paste, and can be made into electrodes or other conductive structures of solar cells by screen printing or coating processes such as scraping, spin coating, slit coating, spraying, etc. Any of the above composite conductive powder materials can be made into conductive ink, and can be made into electrodes or other conductive structures of solar cells by printing.

[0087] The composite conductive powder material of this embodiment is mainly used in solar cells, especially solar cells containing perovskite light-absorbing layers, and can solve the problem of cell efficiency degradation induced by mutual diffusion of metal materials and light-absorbing layer materials (such as halogen ions).

[0088] Embodiment 2

[0089] This embodiment provides a method for preparing a composite conductive powder material. Figure 4 As shown, the method includes:

[0090] S1. Providing metal particles as powder core;

[0091] For example, a commercially available metal powder material with a particle size of 1 to 3 μm or smaller can be selected as the powder core, such as copper powder or silver-coated copper powder.

[0092] The metal particles as the core of the powder are preferably spherical or nearly spherical in shape, but are not limited thereto, and may be, for example, flake or dendritic. Alternatively, spherical or nearly spherical shapes may account for the majority (more than 60%) of the metal particles, while flake or dendritic metals may be mixed.

[0093] S2. Form a coating layer made of an anti-permeation material on the powder core, the coating layer at least partially covers the powder core, and the coating layer is used to prevent the metal of the powder core from diffusing to the outside of the coating layer and other material molecules outside the coating layer from diffusing to the powder core. Exemplarily, the coating layer can be formed using a powder coating device, which can be, for example, a powder magnetron sputtering coating device, a powder cathode arc coating device, or a chemical vapor deposition device.

[0094] The coating material can be a conductive ceramic material or graphene with anti-penetration properties, and the thickness of the coating is about 50nm to 0.3μm. For conductive ceramic materials, the coating can be prepared by powder magnetron sputtering coating, powder cathode arc coating, or atomic layer deposition equipment. For graphene materials, it can be made by chemical vapor deposition equipment (i.e., CVD method). For example, hydrocarbons (such as methane, ethanol, etc.) can be passed into the surface of metal powder materials such as copper and nickel particles that have been heated at high temperature, and the reaction is continued for a certain period of time and then cooled. During the cooling process, carbon atoms will adhere to the surface and diffuse and grow, so that multi-layer or single-layer graphene will be formed on the surface of the particles.

[0095] For example, in a specific implementation example, magnetron sputtering technology can be used to first form a 10-20 nanometer titanium metal layer or chromium metal layer as an adhesion layer on the powder core; and then a conductive ceramic material layer is formed on the adhesion layer as a coating layer using magnetron sputtering technology.

[0096] The method for preparing a composite conductive powder material provided in the present application attaches an anti-permeability material to the surface of a metal powder material that is easy to diffuse, has active chemical properties but high electrical conductivity, to prepare a conductive composite powder material that can ensure that the overall conductivity of the material meets the requirements and reduce the escape of metal ions in the material. The material can be used for low-cost, large-scale electrode preparation methods (such as screen printing, laser transfer, or printing technology, or electrostatic spraying and other film-forming methods), and can avoid or to a certain extent reduce the cell efficiency degradation induced by the use of metal electrodes in solar cells that are sensitive to impurities (such as perovskite and perovskite cells, copper indium gallium selenide cells).

[0097] The oxidation resistance of copper powder is poor. Under the induction of silver, copper is more easily oxidized in silver-coated copper powder. The powder material with a conductive ceramic or graphene coating layer prepared by the method of the present application is low in price and has good oxidation resistance and dispersibility.

[0098] Embodiment 3

[0099] The present embodiment provides a conductive material (such as photovoltaic paste) for solar cells, including the composite conductive powder material described in any of the above embodiments; the conductive material of the present embodiment refers to a raw material for preparing a conductive structure of a solar cell, or a raw material for connecting two conductors. For example, the conductive material of the present embodiment may include a conductive paste and a conductive ink.

[0100] Exemplarily, this embodiment provides a conductive paste, including the composite conductive powder material described in any one of the above embodiments, and also including: an organic polymer binder phase, an organic solvent and an additive, the organic polymer binder phase includes at least one of epoxy resin, acrylic resin, polyurethane, cellulose, silicone resin and rosin, the organic polymer binder phase also includes a curing agent matching the epoxy resin, acrylic resin, polyurethane, silicone resin, etc., the additive includes at least one of a coupling agent, a plasticizer, a defoamer, a thixotropic agent and a wetting agent; the organic solvent includes at least one of esters, ethers, ketones and hydrocarbons.

[0101] In some embodiments, the conductive paste comprises a composite conductive powder material with an average particle size of 2 to 3 μm.

[0102] In another embodiment, the conductive paste may include composite conductive powder materials of various particle sizes, such as composite conductive powder materials with an average particle size of 1 to 3 μm as the main body (not less than 70%), and a small amount of composite conductive powder materials with an average particle size of 10 to 100 nm are doped. The composite conductive powder materials of these two particle size ranges are mixed with an organic polymer binder phase, an organic solvent and an additive to form a conductive paste.

[0103] The conductive paste can be used, for example, to prepare electrodes and electrode leads of solar cells by screen printing, laser transfer, or printing. The conductive paste can also be used to prepare main grids and auxiliary grids for current collection and collection; it can also be used to prepare solder for low-temperature welding.

[0104] The conductive paste of this embodiment can be used as a raw material for screen printing, laser transfer, printing or other coating film forming methods, and can replace silver powder or silver-coated copper powder for preparing low-temperature conductive paste, which is low in price and has good oxidation resistance. The conductive paste of this application can also be used for the electrode layer or conductive layer of solar cells (especially solar cells containing perovskite light-absorbing layers) to solve the problem of cell efficiency degradation induced by mutual diffusion of metal materials and light-absorbing layer materials (such as halogen ions).

[0105] Embodiment 4

[0106] This embodiment provides a solar cell, the electrode of the solar cell is made of any of the above-mentioned composite conductive powder materials or a conductive paste including the same, which can avoid the cell efficiency degradation and stability reduction problems induced by the mutual diffusion of metal materials and light-absorbing layer materials (such as halogen ions).

[0107] Solar cells may include perovskite cells, all-perovskite tandem cells, and perovskite crystalline silicon tandem cells.

[0108] In summary, the composite conductive powder material of the present application is a good high-conductive filler, which can also be added to coatings (paints), glues (adhesives), inks, polymer slurries, plastics, rubbers, etc., and can be made into various conductive and electromagnetic shielding products, which are widely used in the fields of conductivity, electromagnetic shielding, etc. in various industrial sectors such as electronics, electromechanics, communications, printing, aerospace, weapons, etc. For example, the conductivity and electromagnetic shielding of electronic, electrical, and communication products such as computers, mobile phones, electronic medical equipment, and electronic instruments.

[0109] Simulation experiment

[0110] In this experiment, copper wire is used to simulate the powder core formed by metal materials; a layer of titanium nitride material is plated on the copper wire to simulate the coating layer covering the powder core. Figure 5 As shown in Figure 2, the contact resistance of copper wire with titanium nitride coating on the surface of ITO (a transparent conductive layer commonly used in solar cells) is lower than that of conventional tin-clad copper wire (reference Figure 5 However, the copper wire with titanium nitride coating can avoid the problem of cell efficiency degradation caused by the mutual diffusion between the metal of the metal electrode and the perovskite light absorbing layer (or other light absorbing layer materials, or other adjacent or contact layers) due to the anti-permeability of the titanium nitride coating.

[0111] Under the premise of no conflict, the technical features mentioned in this application can be used in any combination. For the sake of brevity, this article will not describe them one by one.

[0112] The present application proposes a solution for perovskite solar cells, but the actual application is not limited to this. It can be applied to all similar scenarios where the performance of solar cells is affected by the diffusion of electrode materials and light-absorbing layer materials.

[0113] Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present application. If no specific techniques or conditions are specified in the embodiments, the conventional techniques or conditions in the art or the product instructions are used, and the reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0114] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A composite conductive powder material, characterized in that: include: A powder core formed of a metal material; and, A coating layer formed of an anti-penetration material at least partially covers the powder core, and is used to prevent the metal of the powder core from diffusing to the outside of the coating layer and other materials outside the coating layer from diffusing to the powder core.

2. The composite conductive powder material according to claim 1, characterized in that: The composite conductive powder material has a core-shell structure, and the coating layer completely covers the powder core.

3. The composite conductive powder material according to claim 1 or 2, characterized in that: The anti-permeability material is at least one of a conductive ceramic material and graphene.

4. The composite conductive powder material according to claim 3, characterized in that: The conductive ceramic material includes at least one of TiN, TiC, TiCN, TiSiN, AlTiN, ZrN, TaN and HfN.

5. The composite conductive powder material according to claim 1 or 2, characterized in that: It also includes an adhesion layer, which is located between the powder core and the coating layer.

6. The composite conductive powder material according to claim 5, characterized in that: When the coating layer is a conductive ceramic material, the adhesion layer includes at least one of a titanium metal layer, a chromium metal layer and a titanium-chromium composite layer.

7. The composite conductive powder material according to claim 1 or 2, characterized in that: The powder core includes at least one of metal element particles and alloy particles; Optionally, the powder core includes at least one of silver particles, copper particles and silver-coated copper particles.

8. The composite conductive powder material according to claim 1 or 2, characterized in that: The particle size or equivalent particle size of the composite conductive powder material is less than 35 μm. Optionally, the particle size or equivalent particle size of the composite conductive powder material is 1 μm-3 μm.

9. The composite conductive powder material according to claim 1 or 2, characterized in that: The thickness of the coating layer is 5nm to 1μm; Optionally, the coating layer has a thickness of 50 nm to 0.3 μm.

10. A method for preparing the composite conductive powder material according to any one of claims 1 to 9, characterized in that: include: Provide metal material as the core of the powder; A coating layer made of an anti-permeation material is formed on the powder core, so that the coating layer at least partially covers the powder core.

11. The preparation method according to claim 10, characterized in that: Using a powder coating device to form the coating layer on the powder core; Optionally, the powder coating equipment includes at least one of powder magnetron sputtering coating equipment, powder cathode arc coating equipment, atomic layer deposition equipment and chemical vapor deposition equipment.

12. The preparation method according to claim 11, characterized in that: The process of forming the coating layer on the powder core by using a powder coating device includes: By using a magnetron sputtering method, a 10nm-20nm adhesion layer is first formed on the powder core; and then the coating layer is formed on the adhesion layer by using a magnetron sputtering method.

13. Use of the composite conductive powder material according to any one of claims 1 to 9 or the composite conductive powder material prepared by the preparation method according to any one of claims 10 to 12 in preparing a conductive structure; Optionally, the conductive structure includes a solar cell electrode, an electrode lead or a grid line.

14. A conductive material for a solar cell, characterized in that: It comprises the composite conductive powder material according to any one of claims 1 to 9 or the composite conductive powder material prepared by the preparation method according to any one of claims 10 to 12; the conductive material comprises conductive paste and conductive ink.

15. The conductive material according to claim 14, characterized in that When the conductive material is a conductive paste, the conductive paste further comprises: an organic polymer binder phase, an organic solvent and an additive; Optionally, the organic polymer bonding phase includes a resin and a curing agent matching the resin, and the resin includes at least one of epoxy resin, acrylic resin, polyurethane, cellulose, silicone resin and rosin; Optionally, the organic solvent includes at least one of esters, ethers, ketones and hydrocarbons; Optionally, the auxiliary agent includes at least one of a coupling agent, a plasticizer, a defoaming agent, a thixotropic agent and a wetting agent.

16. The conductive material according to claim 15, characterized in that In the conductive paste, the composite conductive powder material includes a main powder and a doped powder with different particle sizes, the average particle size of the main powder is 2 μm to 3 μm, and the average particle size of the doped powder is smaller than the average particle size of the main powder; Optionally, the average particle size of the doped powder is 10 nm to 100 nm; Optionally, the mass proportion of the main powder in the composite conductive powder material is greater than or equal to 70%.

17. A solar cell, characterized in that: The electrode of the solar cell is made of the composite conductive powder material according to any one of claims 1 to 9 or the conductive material according to any one of claims 14 to 16.

18. The solar cell according to claim 17, characterized in that: The solar cell includes a perovskite cell, a full perovskite stacked cell or a perovskite crystalline silicon stacked cell.

Citation Information

Cited By

  • Battery piece, preparation method thereof and photovoltaic module

    CN121751815A

  • Solar cell and preparation method thereof, laminated cell and photovoltaic module

    CN122535015A